Dissecting the Financial Relationship Between Industry and Academic Neurosurgery. Issue 6 (11th August 2020) - Motiwala, Mustafa; Herr, Michael J; Jampana Raju, Sripraharsha S; Lillard, Jock; Ajmera, Sonia; Saad, Hassan; Schultz, Andrew; Fraser, Brittany; Wallace, David; Norrdahl, Sebastian; Akinduro, Olutomi; Oravec, Chesney S; et al.
Abstract: BACKGROUND: Established by the Centers for Medicare and Medicaid Services (CMS), the Open Payments Database (OPD) has reported industry payments to physicians since August 2013. OBJECTIVE: To evaluate the frequency, type, and value of payments received by academic neurosurgeons in the United States over a 5-yr period (2014-2018). METHODS: The OPD was queried for attending neurosurgeons from all neurosurgical training programs in the United States (n = 116). Information from the OPD was analyzed for the entire cohort as well as for comparative subgroup analyses, such as career stage, subspecialty, and geographic location. RESULTS: Of all identified neurosurgeons, 1509 (95.0%) received some payment from industry between 2014 and 2018 for a total of 106 171 payments totaling 266 407 458.33. A bimodal distribution was observed for payment number and total value: 0 to 9 (n = 438) vs > 50 (n = 563) and 0-1000 (n = 418) vs >10 000 (n = 653), respectively. Royalty/License was the most common type of payment overall (59.6%; 158 723 550.57). The median number (40) and value (8958.95) of payments were highest for mid-career surgeons. The South-Central region received the most money (117 970 036.39) while New England received the greatest number of payments (29 423). Spine surgeons had the greatest median number (60) and dollar value (20 551.27) of payments, while pediatric neurosurgeons received the least (8; 1108.29). Male neurosurgeons received a greater number (31) and value (6395.80) of payments than their female counterparts (11, 1643.72). CONCLUSION: From 2014 to 2018, payments to academic neurosurgeons have increased in number and value. Dollars received were dependent on geography, career stage, subspecialty and gender.